(untitled) (Medical Forum Monthly, 2024)
Objective: To study Comparison of Negative Appendectomy rate between Alvorado score and Adult Appendicitis score at Idrees Teaching Hospital, Sialkot & Allama Iqbal Memorial Teaching Hospital, Sialkot. Design of Study: Prospective study Place and Duration of Study: This study was conducted at the Emergency department of Idrees Teaching Hospital, Sialkot & Allama Iqbal Memorial Teaching Hospital, Sialkot during April 2015 to April 2017. Materials and Methods: We analyzed data of 1139 appendectomies prospectively over period of 2 years for negative appendectomies at emergency department of Allama Iqbal Memorial teaching Hospital Sialkot. Patients were divided in two groups (Group A 579 cases according to Alvorado score and Group B 560 cases according to Adult Appendicitis Score). Negative appendectomy rate for both groups was calculated after histopathology report. The Performa was designed to record age, gender, positive appendectomies and negative appendectomies. The data was analyzed for results on SPSS version 10. Results: The incidence of appendectomy was highest (42.66%) cases 486 at the age group 15-25 years and this incidence went on decreasing with advancement of age. There was higher incidence (54.52%) 621 cases of appendectomy in male population and (45.47%) 518 cases in female population coming to the emergency department. According to histopathology the incidence of negative appendectomy was (19.22%) 219 cases in group A and (3.59%) 41cases in group B but the incidence of positive appendectomy was (29.32%) 334 cases in group A and (42.58%) 485cases in group B. According to Alvarado (MANTRELS) score the incidence of negative appendectomy was (19.22%) 219 cases but according to adult appendicitis score the incidence of negative appendectomy was (3.59%) 41 cases. Conclusion: It showed that adult appendicitis score is much better than Alvarado score for diagnoses of appendicitis.